Longitudinal investigation of vaccine specific antibody levels and cellular markers of adaptive immune responses in HIV Exposed Uninfected (HEU) and Unexposed (UE) infants - Naidoo, Shalena (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2012.